The Relationship of Pre- and Post-Operative Kidney Function and The Degree of Hydronephrosis Caused by Stones and Malignancy in Patients who Have Had A DJ Stent Installed - Rahman, Eka Yudha; Maulani, Eka Putri; Yasmina, Alfi; Sutapa, Hendra; Akbar, Izaak Zoelkarnain; Ardansyah, Audi; Rudiansyah, Mohammad (JBN (Jurnal Bedah Nasional), 2025)
Aim: This study aims to assess the relationships between ureum, creatinine, GFR and the degree of hydronephrosis, both before and after DJ stent installation. This study also assess the association between ureum, creatinine and GFR before and after the DJ stent placement. Methods: An analytical observational study with a cross-sectional design was conducted. Patients with hydronephrosis caused by urinary stones in RSUD Ulin Banjarmasin during 1 January 2022 until 31 January 2023 were included. Renal function (ureum, creatinine, GFR) and degree of hydronephrosis data were collected. Results: A total of 37 patients were included. Most of them (76,3%) were <60 years old and males (60.5%). There were no significant relationships between ureum, creatinine, and GFR and the degree of hydronephrosis, both before and after DJ stent installation (p> 0.05). There was no significant differences between ureum, creatinine and GFR before and after DJ stent placement. Conclusion: There is no significant relationship between kidney function and the degree of hydronephrosis caused by urinary stones.   Keywords: hydronephrosis, ureum, creatinine, GFR, DJ stent.